Poverty, food consumption, and nutrition during the transition to the market economy in Eastern - Cornia, Giovanni Andrea (American Economic Review, 1994)
Historically, average reported levels of food intake in Eastern Europe have been considerably higher than in most middleincome countries. According to food balance-sheet data, average calories, proteins, and fats in terms of availability per capita rose continuously over the 1961-1988 period and generally exceeded the intake requirements established by the World Health Organization (WHO) (Food and Agriculture Organization, 1991). While it may rightly be argued that these data offer little information about the effective control over food by consumers in different income groups, in the case of pre-reform Eastern Europe, full employment, low income inequality, and low food prices generally ensured a minimal level of food intake even for those in the bottom deciles of the income distribution. While undernutrition did not generally represent a problem, considerable imbalances affected the diet of most people in the region. Particularly in urban areas and among low-income groups, food intake was characterized by a high consumption of cholesterol-rich products (such as eggs and animal fats), sugar, salt, bread, and alcohol and a low intake of good-quality meat, fruit and vegetables, and vegetable oils. The data in Table 1 clearly illustrate this situation for Russia and can be taken as representative of the entire region. Low-income families consumed less food per capita, while their diet was characterized by greater intake, both in relative and absolute terms, of bread and fats and a lower consumption of more nutritious and healthy foods. The dietary imbalances implicit in this consumption pattern caused an abnormally high incidence of nutritionally related health problems, including a high prevalence of overweight people, cardiovascular diseases, micronutrient deficiencies, and anemia. In addition, a fairly high prevalence of low birth weight (LBW) and low breastfeeding rates were common in the region. Inadequate breastfeeding represented a critical nutritional problem for young children, as milk substitutes and baby foods were generally in short supply.